MIS416 Enhances Therapeutic Functions of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells Against Experimental Colitis by Modulating Systemic Immune Milieu - Byung-Chul Lee; Byung-Chul Lee; Nari Shin; Nari Shin; Jin Young Lee; Jin Young Lee; Insung Kang; Insung Kang; Jae-Jun Kim; Jae-Jun Kim; Seung Eun Lee; Seung Eun Lee; et al. (Frontiers in Immunology, 2018)
Human adult stem cells, including umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs), have recently been considered a promising alternative treatment for inflammatory bowel disease (IBD) due to their unique immunomodulatory properties and ability to promote tissue regeneration. However, despite many years of research and pre-clinical studies, results from clinical trials using these cells have been diverse and conflicting. This discrepancy is caused by several factors, such as poor engraftment, low survival rate, and donor-dependent variation of the cells. Enhancement of consistency and efficacy of MSCs remains a challenge for the feasibility of cell-based therapy. In this study, we investigated whether administration of MIS416, a novel microparticle that activates NOD2 and TLR9 signaling, could enhance the therapeutic efficacy of hUCB-MSCs against Crohn’s disease, using dextran sulfate sodium (DSS)-induced colitis model. Colitis was experimentally induced in mice by using 3% DSS, and mice were administered a retro-orbital injection of MIS416 and subsequent intraperitoneal injection of hUCB-MSCs. Mice were examined grossly, and blood, spleen, and colon tissues were subsequently collected for further ex vivo analyses. To explore the effects of MIS416 on the therapeutic process, hUCB-MSCs and primary isolated immune cells were cultured with MIS416, and in vitro assays were performed. Compared to the single administration of hUCB-MSCs, co-administration with MIS416 improved the therapeutic efficiency of the stem cells by significantly alleviating the symptoms of IBD. Interestingly, MIS416 did not exert any direct effect on the immunomodulatory capacity of hUCB-MSCs. Instead, systemically injected MIS416 altered the immune milieu in the colon which caused hUCB-MSCs to be more readily recruited toward the lesion site and to suppress inflammation more efficiently. In addition, considerable numbers of regulatory immune cells were stimulated as a result of the cooperation of MIS416 and hUCB-MSCs. These findings indicate that co-administration with MIS416 enhances the therapeutic potential of hUCB-MSCs by systemically regulating the immune response, which might be an effective strategy for overcoming the current obstacles to stem cell therapy in clinical practice.